Analysis and Review of the Steganographic Techniques - Patil, H.A; Saxena, P (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, the security associated with information over the web has turned into a significant issue. With the aim to take care of the issue, two fundamental procedures are utilized cryptography and Steganography. The two strategies are utilized for information security reason. Cryptography changes the type of the information and Steganography totally hides its core from the clients, aside from the proposed recipient. The steganography implies secured script while cryptography implies mystery composing. In this paper, a strategy is defined which joins these two techniques to give a more productive and successful outcome. In this paper, different steganographic methods have been analyzed. These methods include text hiding, audio hiding, file hiding and image hiding. This paper reviews and analyzes many existing digital image steganographic methods in both the spatial and transform domains